Constructed police knowledge of “marginal movements”: The SPVM’s GAMMA project - Dominique-Legault, Pascal (Criminologie, 2022)
This article contributes to the growing body of sociological and criminological research on the policing of protests and those on society’s margins by analyzing the construction of police knowledge in the context of the implementation of the GAMMA project by the Service de Police de la Ville de Montréal (Montreal Police Service, or SPVM). Creation of this police project, initiated in 2010 but not made public until 2011, was announced as a means of tracking the activities of those seen as marginal or anarchist in the city of Montreal. However, following a two-year-long legal battle, documents obtained through provincial access to information legislation showed that, far from relying solely on criminalizable events, GAMMA’s goals involved problematization of certain social groups on the political margins. Characteristics of marginal movements were implicitly operationalized into visible indicators of possible criminality, as were their specific political convictions. This article explores the subjective nature of the police knowledge underlying the institutionalization of an additional level of police response differentially targeting specific marginal movements. The results are discussed in the context of recent research on protest policing and marginality, particularly the concepts of “strategic incapacitation,” “intelligent control,” and “landscapes of exclusion.”